The attitude of medical and pharmacy students towards research activities: A multicenter approach. - Bhagavathula, Akshaya Srikanth; Bandari, Deepak Kumar; Tefera, Yonas Getaye; Jamshed, Shazia Qasim; Elnour, Asim Ahmed; Shehab, Abdulla (MDPI, 2017)
Abstract: Aim: To assess the attitude of medical and pharmacy students in Asian and African universities towards scholarly research activities. Methods: An anonymous, cross-sectional, self-reported online survey questionnaire was administered to medical and pharmacy students studying in various Asian and African universities through social media between May and July 2016. A 68-item close-ended questionnaire consisting of Likert-scale options assessed the students’ research-specific experiences, and their attitudes towards scholarly research publications. Results: A total of 512 questionnaires were completed, with a response rate of 92% from Asia and 94% from Africa. More pharmacy students (70.8%) participated than medical students (29.2%). Overall 52.2% of the pharmacy students and 40% of medical students believed that research activities provided a means of gaining respect from their faculty members. Lack of encouragement, paucity of time, gaps in research activities and practices, and lack of research funding were some of the most common barriers acknowledged by the students. A nonparametric Mann-Whitney test showed that a statistically significant difference was observed, in that more than 80% of the pharmacy students viewed scientific writing and research activities as valuable experiences (p = 0.001) and would like to involve their co-students in scholarly research activities (p = 0.002); whereas the majority of the medical students desired to be involved more in scholarly research publications (p = 0.033). Conclusion: Pharmacy students had good attitudes towards research activities and a higher number of medical students desired to be involved more in research publications. Faculties may consider taking special research initiatives to address the barriers and improve the involvement of medical and pharmacy students in scholarly research activities.